2010
DOI: 10.1002/ajp.20884
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of gastro‐intestinal parasites and commensals as an index of population and ecosystem health: the case of sympatric western chimpanzees (Pan troglodytes verus) and guinea baboons (Papio hamadryas papio) at Fongoli, Senegal

Abstract: The exponential decline of great apes over the past 50 years has resulted in an urgent need for data to inform population viability assessment and conservation strategies. Health monitoring of remaining ape populations is an important component of this process. In support of this effort, we examined endoparasitic and commensal prevalence and richness as proxies of population health for western chimpanzees (Pan troglodytes verus) and sympatric guinea baboons (Papio hamadryas papio) at Fongoli, Senegal, a site d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 24 publications
3
54
0
1
Order By: Relevance
“…The survival of the West African Chimpanzee is, therefore, a very high conservation priority. carried out a large-scale survey (more than 100 villages surveyed) of its distribution area in Senegal, but according to Carter filtering Galat-Luong et al 2009), nesting behavior (Stewart et al 2007;, intestinal parasites (Howells et al 2011) and seed reingestion (Bertolani & Pruetz 2011). For the present study we assessed the influence of the season and topography on the distribution of Pan troglodytes verus Chimpanzees within their habitat outside of the PNNK, which is not previously reported.…”
Section: Issnmentioning
confidence: 95%
“…The survival of the West African Chimpanzee is, therefore, a very high conservation priority. carried out a large-scale survey (more than 100 villages surveyed) of its distribution area in Senegal, but according to Carter filtering Galat-Luong et al 2009), nesting behavior (Stewart et al 2007;, intestinal parasites (Howells et al 2011) and seed reingestion (Bertolani & Pruetz 2011). For the present study we assessed the influence of the season and topography on the distribution of Pan troglodytes verus Chimpanzees within their habitat outside of the PNNK, which is not previously reported.…”
Section: Issnmentioning
confidence: 95%
“…Of these, E. coli is one of the most commonly reported human protozoa (Chunge et al, 1991;Youn, 2009;Boeke et al, 2010). It has also been recovered dogs, nonhuman primates (Howells et al, 2011), and marsupials (CamposFilho et al, 2008;Youn, 2009). Previous report suggested that E. polecki to be zoonotic but recent molecular diagnosis suggested that this species is restricted to humans only whereas E. hartmanni is potentially zoonotic and reported in non-human primates (Stensvold et al, 2011).…”
Section: Giardia Spmentioning
confidence: 99%
“…By far the most common reported non-human primate host has been the baboon, and the dominant parasite in these instances has been Schistosoma mansoni, although one observation of a baboon infected with S. haematobium was made from South Africa in the 1990s (Appleton and Henzi, 1993). Observations have been equally as widespread in the last two decades as in earlier years, with accounts of infection from Kenya (Hahn et al, 2003, Tanzania (Muller-Graf et al, 1997, Murray et al, 2000, Ethiopia (Legesse andErko, 2004, Phillips-Conroy, 1986), Senegal (Howells et al 2011, Mcgrew et al, 1989 and Nigeria (Weyher et al, 2006); baboons have also recently been implicated as potential reservoir hosts for S. mansoni in parts of the Arabian peninsula (Ghandour et al, 1995, Zahed et al, 1996. In several of these cases, as well as other incidences of parasite transmission between humans and non-human primates, it has been suggested that forest fragmentation, increased proximity of humans to wild habitats and the emerging reliance of wild primates on human settlements for food (such as through crop-raiding) is at least partially responsible for increased exposure and risk of these animals contracting 'human' diseases (Gillespie andChapman, 2008, Weyher et al, 2006).…”
Section: Schistosomiasis In Non-human Primates In Africamentioning
confidence: 99%
“…Similarly, Legesse and Erko (2004) observed schistosomiasis infection in baboons in Ethiopia, but not in sympatric vervet monkeys. Infected baboons have also been reported from two localities, Fongoli in Senegal and Gombe Stream National Park in Tanzania, which are also inhabited by troops of chimpanzees; despite extensive parasitological surveys, these chimpanzees have never convincingly displayed positive infection with S. mansoni (Bakuza and Nkwengulila, 2009, Howells et al, 2011, Muller-Graf et al, 1997, Murray et al, 2000. There is an isolated, unpublished account, from the early 1990s, of S. mansoni eggs being recovered from chimpanzee stool in Gombe Stream NP (Nutter, 1993); however, since both earlier and ensuing examinations failed to reconfirm the finding, it may be that this report is a case of mislabeled samples, and the stool had actually belonged to a baboon.…”
Section: Schistosomiasis In Non-human Primates In Africamentioning
confidence: 99%